Pengaruh Formula Pupuk Urea-Zeolit-Arangaktif terhadap pH, N-total, KTK tanah dan Residu Pb pada Tanah Tercemar Limbah Industri - Rija Sudirja; Santi Rosniawaty; Ade Setiawan; Rhendika Indra Yunianto (Soilrens, 2016)
One of the factors inhibiting the production of rice is not efficient in the use of fertilizers and ecosystem damage due to toxic hazardous materials such as heavy metals. the use of Urea, Zeolite, Activated charcoal based fertilizer is expected to increase the production of paddy rice crops in rice fields heavy metal contaminated. The experiment was conducted in the village of the District Linggar Rancaekek Regency  Bandung from  March  to  May  2015.  The experiment  used  randomized  block design with four single  treatment,  that  is  A =  urea  : zeolite  (95:5),  B  =  urea  : zeolite  : activated charcoal (50:45:5), C = urea : zeolite : activated charcoal (50:25:25), D = urea : zeolite (60:40), each with  five replicates.  Rice  varieties  used are Inpari  30.  The  results  showed  that  administration RS fertilizer formula  is  proven to  reduce  the  solubility  of  approximately  30%  Pb  and increases  the cation exchange capacity  (CEC) of  the soil.  RS fertilizer no  real  effect  on pH and N-Total  soils. Formulation urea : zeolite : activated charcoal (50:25:25) can decrease the solubility of Pb, while the CEC best demonstrated by the increase in formulation urea : zeolite : activated charcoal (50: 45: 5). Key words: heavy metals, RS fertilizer, wetland rice